(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article presents the basic methods of teaching a foreign language to preschoolers and discusses the importance of applying educational games in the teaching process. The study reveals the factors of creating favorable conditions for mastering language and speech skills.